Diversity and composition of shrubs in Behali Reserve Forest of Biswanath district, Assam, with special emphasis on Gnetum gnemon L. - Borah, Dipankar; Das, Niku; Mihu, Inda; Hajong, Bipankar; Tangjang, Sumpam (Ecological Questions, 2022)
The study is focused to study the diversity and distribution of shrubs in the Behali Reserve Forest. A total of 46 species of shrubs belonging to 40 genera representing 25 families were documented. Rubiaceae and Lamiaceae were the dominant families. Pycnarrhena pleniflora has the highest IVI value of (48.25) followed by Coffea benghalensis (41.1). Plotting in Raunkiaer’s frequency class distribution it was found that the shrub community of BRF is heterogeneous in nature i.e. represents uniform species diversity which does not allow the dominance of a species. Among the recorded shrubs, Pycnarrhena pleniflora, Coffea benghalensis, Boeica filiformis, Gnetum gnemon and Dalhousiea bracteata has a good population status. Gnetum gnemon on the other hand a potential NTFP of BRF has an infrequent distribution which is due to its high economic value and unregulated collection. The market value of G.gnemon and its conservation needs are also presented.